Pembuatan Konten Kreatif Bagi Calon Lulusan SMA Untuk Mengahadapi Dunia Profesional - Achwan Noorlistyo Adi; Muhammad Rajby Nur Alawy (LPPM Universitas Informatika dan Bisnis Indonesia, 2025)
The purpose of the implementation of the community service program is to improve the ability of students to create creative content in the midst of exposure to technological advances that present various kinds of content. Therefore, we explain the material about tips and tricks to create creative content and provide insight to the audience to be able to analyze the content that is trending. Thus, it is necessary to increase the ability to create creative content to deal with the professional world. This training activity was carried out face to face at SMAN 16 Bandung and lasted for 1 day. The output of this activity is in the form of an increase in the ability of students of SMAN 16 Bandung to create creative content, improve the ability to analyze content that is trending, as well as the practice of making storylines based on unrest and participants' experiences and creative creance of creative content.